CASC9 plays a role in salivary adenoid cystic carcinoma in vitro by upregulation of ACLY. (5th January 2021) - Xie, Hongliang; Tang, Jianming; Lu, Lu; Li, Bohan; Wang, Mengmeng
Abstract: Objective: The study was designed to explore the role of cancer susceptibility candidate 9 (CASC9) in salivary adenoid cystic carcinoma (SACC) (SACC‐83 and SACC‐LM) cell malignant phenotypes. Methods: Colony formation assay was used to measure cell proliferation. Transwell assay was used to detect cell migration and invasion. Flow cytometry analysis was applied to determine cell cycle distribution and apoptosis. FISH assay revealed the subcellular location of CASC9. Results: Downregulation of CASC9 inhibited SACC cell proliferation, migration, and invasion, led to cell arrest at G0/G1 phase, and facilitated cell apoptosis. In mechanism, CASC9 bound with microRNA 146b‐5p (miR‐146b‐5p) and negatively modulated miR‐146b‐5p expression. MiR‐146b‐5p directly targeted 3' untranslated region of ATP‐Citrate Lyase (ACLY) to degrade ACLY in SACC cells. CASC9 upregulated ACLY expression through competitively binding with miR‐146b‐5p. Furthermore, rescue assays indicated that ACLY overexpression counteracted the effects triggered by CASC9 knockdown on cell proliferation, migration, invasion, and apoptosis in SACC cells. Conclusion: CASC9 facilitated the malignant phenotypes of SACC cells by the regulation of the miR‐146b‐5p/ACLY axis. These findings might lay foundation for SACC research.